Bahan Organik Total dan Kelimpahan Bakteri di Perairan Teluk Benoa, Bali - Yuspita, Ni Luh Eta; Putra, I Dewa Nyoman Nurweda; Suteja, Yulianto (Journal of Marine and Aquatic Sciences; Vol 4 No 1 (2018)DO - 10.24843/jmas.2018.v4.i01.129-140, 2017)
Benoa Bay is semi-enclosed waters that have various activities. The existence of these activities will contribute to organic matter in the waters so that the effect on the presence of bacteria. This study aims to determine the total concentration of total organic matter (TOM) and bacterial abundance as well as its spatial and temporal distribution, and to determine the relationship of TOM concentration to bacterial abundance in the waters of Benoa Bay. Data collection is conducted on the surface of the waters in December 2016 to February 2017 when ebb conditions at 5 Benoa Bay water stations. Measurement of organic matter using permanganate test in titimetry based on standard methods SNI 06-6989.22-2004. Measurement of bacterial abundance using Total Plate Count (TPC) method. The TOM concentrations ranged from 63.20 to 65.10 mg/l and bacterial abundances ranged from 30 to 300 CFU/ml. Spatial distribution of TOM concentration and bacterial abundance tends to be higher close to Suwung Landfills (TPA) activity, floating net cage cultivation (KJA) activity in Serangan waters, and Buaji river estuary and tend to be lower approaching Benoa harbor activity and waters further from those activities. The concentration of TOM and bacterial abundance in December 2016 to February 2017 have fluctuating values. Based on the interpretation of the correlation coefficient, the level of relationship between BOT concentration and bacterial abundance in the waters of Benoa Bay is quite strong.